2023
DOI: 10.3390/ma16031205
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Laser Structuring of Tungsten Carbide Cutting Tools for Improving Their Tribological Performance in Turning Aluminum Alloy Al6061 T6

Abstract: In times of societal development, sustainability has become a major concern for many manufacturers in the metal industries. In this context, surface texturing of cutting tools offers a promising approach in terms of reducing energy consumption and material waste. In this work, direct laser interference patterning is utilized for producing periodic line-like structures with spatial periods of 2.0 µm and 5.5 µm on rake-flank faces of cemented tungsten carbide cutting inserts. Structure depths up to 1.75 µm are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…It was reported that the energy concentration increases proportionally with the grain size, as the coarse WC grains act as barrier for the energy dissipation due to their high thermal conductivity 24 . According to this, eruptions of the overheated material occurred, resulting in several structure damages for the smallest spatial period 22 .…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…It was reported that the energy concentration increases proportionally with the grain size, as the coarse WC grains act as barrier for the energy dissipation due to their high thermal conductivity 24 . According to this, eruptions of the overheated material occurred, resulting in several structure damages for the smallest spatial period 22 .…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, the reduction in feed force Ff by 28 % compared to the other forces. As a result, the configuration 1 exhibited the best frictional behavior due to the correlation between feed forces and frictional forces for a zero-rake angle 22 . Furthermore, the obtained average oil contact angles for both investigated cutting fluids (CIMSTAR, BIOWAS) are shown in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations